The Choice of Local Food Products by Young Consumers: The Importance of Public and Private Attributes - Fernández-Ferrín, Pilar; Bande Videla, Belén; Calvo-Turrientes, Aitor; Galan-Ladero, M Mercedes (Agribusiness, 2017)
In this paper, we propose an explicative model for the effective purchase of various brands of local products, incorporating private and public motivations into a causal chain and considering product availability as a possible moderator of the effects of these purchase factors on local products. The results obtained by applying conditional process analysis and a Tobit model to the responses of 195 young consumers show that local identity can have direct and/or indirect effects on the effective purchase of four different brands of local, traditional, and nontraditional products. Furthermore, for two of these brands, perceived product availability moderates the relationship between product valuation and effective purchase.
Keywords: JCR; Scopus